THE RELATIONSHIP OF ADOLESCENT KNOWLEDGE ON THE BEHAVIOR OF PERSONAL HYGIENE DURING MENSTRUATION : A LITERATURE REVIEW - Rozy Dian Putri Rozy; Gatut Hardianto; Endyka Erye Frety (Indonesian Midwifery and Health Sciences Journal, 2022)
Background: Reproductive health is a vital issue in health development that impacts people's mortality, morbidity and life expectancy. The importance of maintaining reproductive health because it can cause diseases, namely reproductive tract infections, especially in young women. WHO data 2007 the highest incidence of reproductive tract infections occurs in adolescents, namely 35%-42%. The purpose of this study was to determine the relationship between the level of knowledge of young women to the behavior of maintaining personal hygiene of the genital organs during menstruation. Method : the method used is literature review. For data using 5 primary research journals on google scholar with the keywords menstrual hygiene, knowledge, personal hygiene obtained free of charge. Results: The level of knowledge and age influence a person's behavior in maintaining personal hygiene during menstruation. Conclusion: Based on all the literature that has been reviewed, it can be concluded that there is a relationship between the level of knowledge and personal hygiene behavior during menstruation.  Keywords : Menstrual Hygiene, Knowledge personal Hygiene,